Metamorphosis of the US foreign security policy in the 21st century - Pospíšil, Tomáš; Dvořáková, Vladimíra, 1957-; Školkayová, Marta, 1984-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The dissertation identifies and analyzes metamorphosis of the US foreign security policy in the 21st century. The main aim is also to identify whether the United States entered a new era with the attacks of 9/11 and whether so called the Bush doctrine was an appropriate reaction to the global terrorism. The thesis is divided into three chapters. The first chapter describes the US security strategies since WWII. In the second chapter, foreign security policy of George W. Bush and its metamorphosis is analyzed. The last chapter is devoted to the security strategies of Barack Obama.
Vedoucí práce: Vladimíra Dvořáková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní a evropská studia - diplomacie [obor dipl. práce]; diplomové práce; master's theses